2004
DOI: 10.1128/aem.70.3.1865-1868.2004
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite-Oxidizing Hydrogenobaculum Strain Isolated from an Acid-Sulfate-Chloride Geothermal Spring in Yellowstone National Park

Abstract: An arsenite-oxidizing Hydrogenobaculum strain was isolated from a geothermal spring in Yellowstone National Park, Wyo., that was previously shown to contain microbial populations engaged in arsenite oxidation. The isolate was sensitive to both arsenite and arsenate and behaved as an obligate chemolithoautotroph that used H 2 as its sole energy source and had an optimum temperature of 55 to 60°C and an optimum pH of 3.0. The arsenite oxidation in this organism displayed saturation kinetics and was strongly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 17 publications
3
81
2
Order By: Relevance
“…Are these compounds true enzymatic inhibitors? A concentration of 60 M sulfide has been observed to completely stop As III oxidation in whole cells of Hydrogenobaculum at low pH (48), whereas sulfide has been reported to strongly enhance the As III oxidation in Mono Lake samples at high pH (58). However, did sulfide act on the Aro directly in these cases?…”
Section: IIImentioning
confidence: 89%
See 1 more Smart Citation
“…Are these compounds true enzymatic inhibitors? A concentration of 60 M sulfide has been observed to completely stop As III oxidation in whole cells of Hydrogenobaculum at low pH (48), whereas sulfide has been reported to strongly enhance the As III oxidation in Mono Lake samples at high pH (58). However, did sulfide act on the Aro directly in these cases?…”
Section: IIImentioning
confidence: 89%
“…63, 64 for original works). More recently, the interaction between As III oxidation and sulfur metabolism was addressed (48,58,65), but it has not been studied at the molecular level prior to this work. Although ability of Aro to use cyt c 552 as electron acceptor may be interpreted as a possible cross-talk between sulfur and arsenic metabolisms, this merging of electron transfer pathways is not obligatory because Aro possesses a second, dedicated, acceptor, i.e.…”
Section: IIImentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6, 13, 40); and, most recently, in anoxic photosynthesis (21, 33). Likewise, progress has been made in the understanding of the biochemistry of the As III oxidase enzyme (1,14,37 oxidase structural genes were later cloned from the above-mentioned Rhizobium NT-26 organism (53).…”
mentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 99%
“…Analytical As chemistries were determined using techniques previously described (10). Briefly, cell suspensions were centrifuged and supernatants were filtered (0.22-m pore size) into two separate 15-ml bottles (5 ml each).…”
Section: Methodsmentioning
confidence: 99%